Comparison of myofascial release after passive muscle stretching and neural mobilization on ROM of the hip. - Mendes, Alan Campelo; Muniz, Maria Moreira; Silva, Rayany Gysely Miranda da; Lopes, Rauena Souto Diogo; Carvalho, Fabiana Teixeira de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The hip joint is one that has more stability, but on the other hand has less mobility with respect to the shoulder joint, due to its greater amount of muscle tissue and ligaments. This large amount of muscles can undergo changes that hinder the amplitude motion, and shortening a key, with the posterior region of the thigh among the hardest hit targets. The neural mobilization and stretching myofascial release have benefits against this change. Objective: To compare effects of myofascial release is followed by a passive muscle stretching relation to neural mobilization on range of motion of the hip. Method: The study consisted of a quantitative, prospective research, intervention, descriptive and analytical sample composed of 57 participants divided into three groups of 19 people who remained as follows: group G1 neural mobilization, intervention applied to the sciatic nerve which innervates the muscles concerned, G2 myofascial release followed by stretching passive muscle in the posterior thigh and the control group G3 which served Just for comparison and without any intervention. Participants were evaluated before the application of technical and after three days of intervention. The angulation was performed by a software program known for CorelDRAW X5. Results: There were statistically analyzed using the statistical software “R” and “SPSS “, and the Wilcoxon test. The G1 presented a average of 8.37 ° (p = 0.0004194), the 7.53 ° (P = 0.000003815) G2 and G3 5 (p = 0.003918). Conclusion: The techniques were statistically significant for obtaining improved ADM (p <0.05), with neural mobilization acquiring greater gain. Suggest studies with new protocols to new scientific evidence.